Pengaruh Implementasi Sistem Informasi Keuangan Daerah dan Kinerja Pegawai - Dona Primasari (Department of Accounting-Faculty of Economic and Business (FEB), 2017)
The objective of this research is to analyze the influence of effectiveness of regional financial information system to officer performance,with the quality of information of financial report as intervening variable.Data was collected by 61 officer of SKPD Banyumas. The analysis method used is path analysis. The result of the analysis shows: (1) a strong influence between effectiveness of regional financial information system to officer performance (2) a moderate influence between effectiveness of regional financial information system to officer performance with the quality of information of financial report.